Endoscopic Adenoidectomy with Microdebrider Versus Conventional Adenoidectomy (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Adenoidectomy is one of the most common surgical procedures performed in children in Bangladesh. Though conventional curettage is highly popular as it has the advantage of being cost effective and continues to be a commonly used method especially in developing countries but Microdebrider has opened the new horizon in this arena. To compare conventional curettage adenoidectomy and endoscopic-assisted powered adenoidectomy using a microdebrider.Materials and methods: This is randomized single blinded comparative study, which was performed in the Medical Center Hospital, Chattogram from August 2019 to July 2020. A total of 60 patients were randomly divided into two groups. Group I underwent conventional curettage adenoidectomy while Group II underwent endoscopic- assisted powered adenoidectomy. Duration of surgery, amount of intra-operative bleeding, adequateness of removal and damage to the adjacent structures were assessed and compared between two groups. All patients were followed for 12 months. Statistical analysis was done using statistical software package SPSS v 22.0. Data were represented as mean ± SD. Continuous variables were compared using the were using the t test while nonparametric data were compared using Mann-Whitney U test. The c2 test was used to compare the nominal data. A p value